2019
DOI: 10.19087/jveteriner.2019.20.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Aflatoxin M1 Exposure through Consumption of Various Dairy Milk Products in Yogyakarta, Indonesia (ESTIMASI PAPARAN AFLATOKSIN M1 MELALUI KONSUMSI BERBAGAI PRODUK SUSU DI YOGYAKARTA, INDONESIA)

Abstract: This study was conducted to investigate the occurrence of aflatoxin M1 (AFM1) in various milk products marketed in Yogyakarta Province (Indonesia) and to estimate the exposure of aflatoxin through contaminated milk consumption. Fresh milk (n=20), pasteurized milk (n=16), and recombined milk products (n=6) were sampled for AFM1 concentration testing by a competitive ELISA test using ELISA kit for AFM1 assay. A survey was conducted to interview consumers (n=88) on milk consumption habit (milk type and amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
1
1
Order By: Relevance
“…A recent study was conducted in Yogyakarta province in Sleman, Yogyakarta, and Kulon Progo Districts. The results showed that 92.5% of samples were contaminated with AFM1 in a range of 24-570 ng/L and levels of AFM1 contamination were within Indonesian regulatory limit (Sumantri et al 2019). Our results are different in levels of contamination from most previous studies around Indonesia, but some of them are within the Indonesian national standards and others higher than the limits, this limit of contaminations might be the main cause of hazards and risks to human health around the country.…”
Section: Discussioncontrasting
confidence: 85%
“…A recent study was conducted in Yogyakarta province in Sleman, Yogyakarta, and Kulon Progo Districts. The results showed that 92.5% of samples were contaminated with AFM1 in a range of 24-570 ng/L and levels of AFM1 contamination were within Indonesian regulatory limit (Sumantri et al 2019). Our results are different in levels of contamination from most previous studies around Indonesia, but some of them are within the Indonesian national standards and others higher than the limits, this limit of contaminations might be the main cause of hazards and risks to human health around the country.…”
Section: Discussioncontrasting
confidence: 85%
“…Earlier, Nuryono et al (2009) [21] also reported AFM1 content in fresh milk collected from Yogyakarta. A surveillance conducted by Sumantri et al, (2019) [22] revealed the presence of AFM1 in various dairy milk products from Yogyakarta. AFM1 was detected in 92.5% of 42 samples at an averaged concentration of 216 ng/L.…”
Section: Introductionmentioning
confidence: 99%